Thromboelastography for Evaluation of Coagulopathy in Nonbleeding Patients with Sepsis at Intensive Care Unit Admission - Muzaffar, Syed Nabeel (Indian J Crit Care Med, 2017)
BACKGROUND: Thromboelastography (TEG) is a global test of coagulation which analyzes the whole coagulation process. TEG is popular in trauma, liver transplant, and cardiac surgeries, but studies in sepsis are limited. We have assessed the utility of TEG for evaluating coagulopathy in nonbleeding patients with sepsis. MATERIALS AND METHODS: A prospective, observational study was done in 12-bedded Intensive Care Unit (ICU) of a tertiary care hospital in North India, during May 2014-November 2014. After ethical clearance, all patients at ICU admission with sepsis were included in the study. Exclusion criteria were age <18 years, plasma/platelet transfusion before admission, patients on oral antiplatelets/anticoagulants, or with underlying hematological disorders. At admission, blood samples for TEG were analyzed by kaolin-based TEG analyzer within an hour of collecting 2.7 ml citrated blood from arterial line. TEG parameters included reaction time (R), K time (K), alpha angle (a), maximum amplitude (MA), coagulation index (CI), and lysis index (LY 30). RESULTS: In TEG, mean values of R, K, a, MA, CI, and LY30 were 6.45 ± 2.59 (min), 1.67 ± 0.96 (min), 66.37 ± 10.44 ((0)), 67.08 ± 10.33 (mm), 0.63 ± 3.46, and 2.23 ± 4.08 (%), respectively. In conventional coagulation assay (CCA), mean values of international normalized ratio (INR), platelet, and fibrinogen were 1.63 ± 0.57, 153.96 ± 99.16 (×10(3) /mm(3)), and 301.33 ± 112.82 (mg/dl), respectively. In those with deranged INR (INR ≥1.6), 60% were normocoagulable and 20% were hypercoagulable. Similarly, 81% patients with thrombocytopenia (platelet count <1,00,000/mL) were normocoagulable. CONCLUSION: TEG could differentiate among normocoagulant, hypocoagulant, hypercoagulant states (unlike CCAs). Patients with septic shock had trend toward hypocoagulant state while those without shock had trend toward hypercoagulant state.